Study on Mechanical Model for Postpeak Shear Behavior of Rock Joints Based on Degradation Characteristics of the 3D Morphology - Juan Liu; Feng Gao; Yan Xing; Xianghe Gao (Advances in Civil Engineering)
The 3D morphology of the joint surface significantly influences the shear behavior of the jointrock. Constant normal load (CNL) direct shear tests with different shear displacement were conducted to understand the shear stress changing with joint roughness and damage degree during shear. The rough joint specimens were prepared using 3D scanning and printing techniques, and shear tests with different normal stresses and shear displacements were performed. Four different parameters and the damaged area quantitatively described by the image binarization and box dimension were calculated and compared to study the roughness evolution of joint surfaces. The experimental results demonstrated that the roughness parameter and shear stress decrease and approach constant values with increasing shear displacement. A JRC degradation model was presented based on regression analyses to evaluate the JRC values of rock joints under various displacements to replace it in the JRC–JCS model. Additionally, a new postshear behavior modeling was proposed for rock joints based on surface degradation characteristics under various initial joint roughness coefficients (JRC0) and normal stress. The stress–displacement curves resulting from the proposed modified model work well in predicting the postpeak stress–displacement curve, which can prove the effectiveness of the postpeak shear behavior modeling.